Globalización y participación política en el mundo moderno. Douglas Chalmers, ''An End to Foreign Policy: The U. S. and Internationalized Politics", Conference Paper 60, The Columbia University, 1991. ; Douglas Chalmers, "The International Dimensions of Political lnstitutions in Latín America: an internationalized politics approach", ponencia presentada ante el 1992 Annual Meeting of the American Political Science Association, septiembre, 1992. ; Zsuzsa Hegedus, "Social Movements and Social Change in Self-Creative Society: New Civil Initiatives in the International Arena Globalization, Knowledge and Society", Sage Publication, Londres, 1990 (también en Intemational Sociolgy, vol 4, núm l, pp. 19-31). ; David Held, "Sovereignty, Nacional Politics and the Global System", publicado por primera vez en 1988 en Political Theory and the Modern State, Polity Press, Oxford, 1989. ; David Held, "Democracy, the Nation-State and the Global System" en Political Theory Today, David Held Editor, Standford University, California, 1991. ; Evan Luard, The Globalization of Politics, The Changed Focus of Political Action in the Modern World, MacMillan, Londres, 1990. - Zabludovsky, Gina (Revista Mexicana de Sociología, 2024)
Se puede afirmar que, en general, los autores que analizan la realidad actual en términos de una "globalización del mundo", aluden a un proceso que abarca tanto los alcances internacionales de las actividades económicas, políticas y sociales como la intensificación de otros niveles de interacción mediados por la moderna industria de la tecnología informativa y la comunicación masiva.